Enacting a people-centred curriculum in elt with teenage learners (2014)
In this paper we reflect on the extent to which the learner-centred curriculum in English language teaching includes teachers and learners. We briefly describe the top-down nature of curriculum development in Argentina, then describe and discuss personal and collaborative explorations based on our identities as teachers of English in secondary education with a people-centred approach in the classroom. Through this paper we wish to highlight pedagogies and teacher strategies which are enacted for and from the classroom and built around both teachers and learners. Recommendations for policy makers are included.En este artículo reflexionamos sobre la medida en que el currículo basado en el estudiante incluye a docentes y estudiantes. Describimos la naturaleza descendente del desarrollo curricular en Argentina y discutimos exploraciones personales y colaborativas, basadas en nuestras identidades como profesores de inglés en la escuela secundaria, dirigidas hacia un enfoque que incluya los actores áulicos. Mediante este artículo buscamos resaltar aquellas pedagogías y estrategias docentes vividas desde y para el aula y construidas alrededor tanto de docentes como de estudiantes. El artículo incluye recomendaciones para autoridades ministeriales.